217k views
3 votes
16. Solve the equation
3x + (2x + 6) = 6x + 1.152

2 Answers

1 vote

Answer:

Answer: x=4.848

Explanation:

Step 1: Simplify both sides of the equation.

3x+2x+6=6x+1.152

(3x+2x)+(6)=6x+1.152(Combine Like Terms)

5x+6=6x+1.152

5x+6=6x+1.152

Step 2: Subtract 6x from both sides.

5x+6−6x=6x+1.152−6x

−x+6=1.152

Step 3: Subtract 6 from both sides.

−x+6−6=1.152−6

−x=−4.848

Step 4: Divide both sides by -1.

−x

−1

=

−4.848

−1

x=4.848

User Adlag
by
5.0k points
4 votes

Answer: X=4.848

Explanation:

User Steoates
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.